Peningkatan Manajemen Rumah Baca Melalui Aplikasi Slims 8 di Masjid Ar-Ridlo Desa Belung Kecamatan Poncokusumo Kabupaten Malang - muthmainnah, muthmainnah; Sasmitaninghidayah, Wiwis; Mardhiyah, Ainatul (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2020)
Improved management of reading houses in the Ar-Ridlo Mosque, Belung Village, Poncokusumo, Malang District. The application used is SLIMS 8. The Senayan Library Management System (SLiMS) is an open source library management system (library management system) licensed under GPL v3. The steps we have taken are making a cataloging module, making a tracking module, creating a circulation module, making a membership management module, making a collection inventory module, making a series of serial management modules and a workshop on reading house management based on Slims 8. A management workshop has been conducted with material install programs, carry out an inventory of books, register members, save and borrow activities, member card printing and book numbers